The Impact Of Video Marketing On The Consumer Behavior Of Generation - Munawar Dilles, Dara Aulia (Digital Repository of Theses, 2025)
This thesis will show how video marketing has effects on the consumer behavior of Generation Z consumers. Generation Z consumers are the most likely segment of the population to be digitally native and have different preferences and expectations for content compared to other generations with an emphasis on visual and interactive engagement. This thesis has examined secondary data, case studies, brand engagement, and digital engagement which exist across a variety of platforms, including TikTok, YouTube, and Instagram, with regard to three specific themes of storytelling, authenticity, and influencer partnerships. Furthermore, the central research question examined how we may think about engagement and influences that contribute to the consumer journey for Gen Z consumers. Based on the analysis, the key findings illustrate how short-form, interactive, and emotionally-driven video marketing are all delivering a best-case scenario engagement to prospective consumers as compared with traditional advertising. Additionally, the research provides practical insights and considerations for brands to negotiate strategies that account for strengths assigned to each platform, whether they align with Gen Z preferences (e.g., co-creation), or offer a transparent engagement aligned with Gen Z (e.g., advocacy with purpose statements). This research is key to advancing emerging literature examining consumer behavior in digitally native attitudes and actions, and to giving sound advice to marketers as they navigate a rapidly moving media landscape.